2021
DOI: 10.7717/peerj.12395
|View full text |Cite
|
Sign up to set email alerts
|

De novoassembly and functional annotation of blood transcriptome of loggerhead turtle, andin silicocharacterization of peroxiredoxins and thioredoxins

Abstract: The aim of this study was to generate and analyze the atlas of the loggerhead turtle blood transcriptome by RNA-seq, as well as identify and characterize thioredoxin (Tnxs) and peroxiredoxin (Prdxs) antioxidant enzymes of the greatest interest in the control of peroxide levels and other biological functions. The transcriptome of loggerhead turtle was sequenced using the Illumina Hiseq 2000 platform and de novo assembly was performed using the Trinity pipeline. The assembly comprised 515,597 contigs with an N50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
(132 reference statements)
1
0
0
Order By: Relevance
“…The upregulation of these pathways was correlated with Huntington's disease, followed by Parkinson's disease, oxidative phosphorylation, Alzheimer's disease, and microbial metabolism in diverse environment signaling pathways (Zhou et al, 2020 ). Furthermore, our study found that posttranslational modifications, protein turnover, chaperones, amino acid transport, and metabolism were significantly increased in MI patients, and similar findings were reported in previous studies on different diseases (Liu et al, 2015 ; Wang et al, 2017 ; Hernández-Fernández et al, 2021 ), although the direct role of these pathways in MI is still not clear. According to our knowledge, the predicted functional metabolic COG pathway in MI patients was explored for the first time in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The upregulation of these pathways was correlated with Huntington's disease, followed by Parkinson's disease, oxidative phosphorylation, Alzheimer's disease, and microbial metabolism in diverse environment signaling pathways (Zhou et al, 2020 ). Furthermore, our study found that posttranslational modifications, protein turnover, chaperones, amino acid transport, and metabolism were significantly increased in MI patients, and similar findings were reported in previous studies on different diseases (Liu et al, 2015 ; Wang et al, 2017 ; Hernández-Fernández et al, 2021 ), although the direct role of these pathways in MI is still not clear. According to our knowledge, the predicted functional metabolic COG pathway in MI patients was explored for the first time in our study.…”
Section: Discussionsupporting
confidence: 91%